Transforming Cities - Jewson, Nick; MacGregor, Susanne (Taylor & Francis, 1997)
This collection examines the profound transformations that have characterised cities of the advanced capitalist societies in the final decades of the 20th century. It analyses ways in which relationships of contest, conflict and cooperation are realised in and through the social and spatial forms of contemporary urban life. In particular, the essays focus on the impact of economic restructuring and changing forms of urban governance on patterns of urban deprivation and social exclusion. These processes, they contend, are creating new patterns of social division and new forms of regulation and control.